Antimicrobial Activity of Bacteriocin S760 Produced by Enterococcus faecium Strain LWP760 - E. A. Svetoch; B. V. Eruslanov; V. P. Levchuk; E. V. Mitsevich; I. P. Mitsevich; YU. N. Kovalev; N. K. Fursova; M. G. Teimurazov; YU. G. Stepanshin; L. I. Volodina; I. A. Dyatlov (Антибиотики и Химиотерапия, 2020)
Antimicrobial activity of bacteriocin S760 (enterocin) produced by Enterococcus faecium strain LWP760 was studied. Bacteriocin S760 is a cationic, hydrophobic, and heat stable peptide with the molecular weight of 5.5 kDa and pI of 9.8. Enterocin S760 is shown to inhibit in vitro the growth both of sensitive and resistant to antibacterials gramnegative and grampositive bacteria of 25 species. MICs of the bacteriocin S760 vary between 0.05-1.6 mg/l for Escherichia coli O157:H7, Salmonella typhimurium, Salmonella enteritidis, Campylobacter jejuni, Yersinia enterocolitica, Yersinia pseudotuberculosis, Listeria monocytogenes and Clostridium perfringens, that are main food-borne pathogens, and from 0.4-1.6 mg/l for Streptococcus pyogenes, Streptococcus pneumoniae and Corynebacterium diphteriae. It is also active against antibioticresistant strains of Staphylococcus aureus, Enterobacter cloacae, Acinetobacter baumannii (with MICs of 0.05-3 mg/l), Klebsiella pneumoniae (with MICs of 6 mg/l), Pseudomonas aeruginosa (with MICs of 0.4-25 mg/l), as well against fungi belonging to species of Candida albicans, Candida krusei and Aspergillus niger (with MICs of 0.1-0.2 mg/l). Enterocin S760 is a novel antimicrobial agents useful in medicine, veterinary and food industry.